1996
DOI: 10.1172/jci118856
|View full text |Cite
|
Sign up to set email alerts
|

Increased guanylate cyclase activity is associated with an increase in cyclic guanosine 3',5'-monophosphate in left ventricular hypertrophy.

Abstract: Left ventricular hypertrophy (LVH) produced by aortic valve plication leads to increased myocardial cyclic GMP. We tested whether this was a result of increased soluble guanylate cyclase activity or nitric oxide (NO) synthase and its functional consequences. We used the nitric oxide donor 3-morpholino-sydnonimine (SIN-1) or the NO synthase inhibitor N G -nitro-l-arginine methyl ester (L-NAME) in 12 control and 12 LVH anesthetized open-chest mongrel dogs. L-NAME (6 mg/kg) or SIN-1 (1 g/kg per min) was infused i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
13
0

Year Published

1998
1998
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 33 publications
3
13
0
Order By: Relevance
“…Many studies have shown a decreased responsiveness to catecholamines [4 -8] in the hypertrophied left ventricle. We have shown in previous work not only alterations in the ␤-adrenergic signaling pathways in hypertrophied hearts but also cyclic GMP increases, the second messenger which may also be involved in mechanisms of compensation [9]. We have also observed metabolic and functional changes associated with alterations in the cyclic GMP signal transduction system [10] in our hypertrophy model.…”
Section: Introductionsupporting
confidence: 66%
“…Many studies have shown a decreased responsiveness to catecholamines [4 -8] in the hypertrophied left ventricle. We have shown in previous work not only alterations in the ␤-adrenergic signaling pathways in hypertrophied hearts but also cyclic GMP increases, the second messenger which may also be involved in mechanisms of compensation [9]. We have also observed metabolic and functional changes associated with alterations in the cyclic GMP signal transduction system [10] in our hypertrophy model.…”
Section: Introductionsupporting
confidence: 66%
“…In this study, we observed that the cGMP levels are upregulated in hypertrophied LV, which is consistent with previous observations in mechanically overloaded hypertrophied heart models. 24,25 In our previous study, we showed in hypertrophied myocytes that the direct challenge of 8-bromo-cGMP did not cause either the depression of contraction or intracellular acidification that was observed in normal myocytes. 13 Conversely, we have shown that the basal Na ϩ /H ϩ exchanger activity measured by the recovery from NH 4 Cl-induced intracellular acidosis is similar in control and hypertrophied myocytes.…”
Section: Discussionmentioning
confidence: 90%
“…Both impaired and enhanced NO-dependent coronary artery vasodilation has been found in LVH and heart failure, experimentally and clinically. [2][3][4][5][6][7] Likewise, other groups have reported increased, 8,9 decreased, 3,10 or unaltered 11,12 coronary eNOS expression and activity in spontaneously hypertensive rats and in compensated LVH. LVH is initially adaptive, but it is associated with a progressive decline in LV function and ultimate cardiac failure.…”
mentioning
confidence: 87%